MODEL PEMBERDAYAAN POKDARWIS DESA JOGOYASAN BERBASIS KEARIFAN LOKAL MENDUKUNG KAWASAN WISATA DALAM UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Endang Wuryandini; Antono Herry Purnomo Adhi; Riyanto Riyanto; Dwi Prastiyo Hadi (Universitas Mataram, 2026)
This community service aims to empower the Jogoyasan Village Tourism Awareness Group (POKDARWIS) based on local wisdom in order to support the development of tourism areas and improve community welfare. POKDARWIS partners are faced with several main problems, namely: (1) limited knowledge and skills in processing potential local products such as cassava, sweet potatoes, potatoes, and breadfruit into value-added products; (2) weak organizational management and governance of POKDARWIS; (3) minimal use of digital technology for marketing tourism products and local processing; and (4) low partnership networks with stakeholders and local governments. To answer these problems, community service activities are carried out through several stages with an implementation schedule, namely: (1) socialization of the PKM program on August 26, 2025, (2) training on diversification of local processed products on September 3, 2025, (3) POKDARWIS organizational management training on September 19, 2025, (4) online marketing training on September 26, 2025, (5) forum group discussion (FGD) followed by the signing of a memorandum of understanding (MoU) with stakeholders and local governments on September 26, 2025, and (6) evaluation of activities on September 28, 2025. Partners play an active role in preparing implementation needs so that the program runs according to plan. The results of the activity show real achievements, namely: (1) in the production aspect, there was diversification and an increase in product quality with a 30% increase in production compared to before the activity, (2) in the management aspect, there was a change in the governance of POKDARWIS to be more professional, (3) in the marketing aspect, an online store was formed through the marketplace, and (4) in the partnership aspect, strategic collaboration was established with stakeholders and the government. The outputs of the activity were: (a) a scientific article entitled